Variasi bahasa â€œsapaan pemirsaâ€ pada konsep siaran audio - Eva Mizkat (Universitas Asahan, 2023)
The variety of languages used by speakers or a group of people will shape the variety of languages in sociolinguistic studies. This research discusses the variation of language